Time-dependent modulation of arterial baroreflex control of muscle sympathetic nerve activity during isometric exercise in humans - Ichinose, Masashi; Saito, Mitsuru; Kondo, Narihiko; Nishiyasu, Takeshi (American journal of physiology. Heart and circulatory physiology, 2006)
1 Institute of Health and Sport Sciences, University of Tsukuba, Tsukuba City, Ibaraki; 2 Applied Physiology Laboratory, Toyota Technological Institute, Nagoya; and 3 Faculty of Human Development, Kobe University, Kobe, Japan Submitted 9 August 2005 ; accepted in final form 8 November 2005 We investigated the time-dependent modulation of arterial baroreflex (ABR) control of muscle sympathetic nerve activity (MSNA) that occurs during isometric handgrip exercise (IHG). Thirteen healthy subjects performed a 3-min IHG at 30% maximal voluntary contraction, which was followed by a period of imposed postexercise muscle ischemia (PEMI). The ABR control of MSNA (burst incidence and strength and total activity) was evaluated by analyzing the relationship between spontaneous variations in diastolic arterial pressure (DAP) and MSNA during supine rest, at each minute of IHG, and during PEMI. We found that 1 ) the linear relations between DAP and MSNA variables were shifted progressively rightward until the third minute of IHG (IHG3); 2 ) 2 min into IHG (IHG2), the DAP-MSNA relations were shifted upward and were shifted further upward at IHG3; 3 ) the sensitivity of the ABR control of total MSNA was increased at IHG2 and increased further at IHG3; and 4 ) during PEMI, the ABR operating pressure was slightly higher than at IHG2, and the sensitivity of the control of total MSNA was the same as at IHG2. During PEMI, the DAP-burst strength and DAP-total MSNA relations were shifted downward from the IHG3 level to the IHG2 level, whereas the DAP-burst incidence relation remained at the IHG3 level. These results indicate that during IHG, ABR control of MSNA is modulated in a time-dependent manner. We suggest that this modulation of ABR function is one of the mechanisms underlying the progressive increase in blood pressure and MSNA during the course of isometric exercise. arterial blood pressure; sympathetic nervous system; integrated circulatory regulation Address for reprint requests and other correspondence: T. Nishiyasu, Institute of Health and Sport Sciences, Univ. of Tsukuba, Tsukuba City, Ibaraki 3058574, Japan (e-mail: nisiyasuattaiiku.tsukuba.ac.jp )